Hubungan Antara Pengetahuan, Sikap, dan Dukungan Keluarga dengan Keikutsertaan Pasangan Usia Subur (PUS) dalam Ber-KB di Wilayah Kerja Puskesmas Purwosari Kota Surakarta - Nasrulloh, Ahmad; , Bejo Raharjo, SKM, M.Kes; , Kusuma Estu Werdani, SKM., M.Kes (2015)
THE RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDE, AND FAMILY SUPPORT WITH THE PARTICIPATION OF SPOUSES OF FERTILE AGE (EFA) IN FAMILY PLANNING IN REGION OF PUSKESMAS PURWOSARI SURAKARTA CITY. The successful of family planning program is the involvement of all parties, which are the government institutions, private sectors, and societies as well as the involvement of all members of the family itself. The purpose of this study was to determine and analyze the relationship between knowledge, attitude, and family support with the participation of spouses of fertile age in family planning in Puskesmas Purwosari Surakarta. This research used analytic survey with cross sectional approach. This study was conducted in Puskesmas Purwosari Surakarta. The population in this study was 3,099 spouses of fertile age, with a sample size of 80 people. Sampling technic usedcluster sampling. Data analysis usedchi square. The results showed relatively good knowledge of the respondents (68.75 %), the attitude of the respondents classified as positive (70 %), and family support was classified as good (73.75 %).The statistical analysis showed that there was a relationship between knowledge (p = 0.001), attitude (p = 0.003), and family support (p = 0.016) with the participation of spouses of fertile age in family planning in Puskesmas Purwosari Surakarta.